2021
DOI: 10.1089/apc.2020.0236
|View full text |Cite
|
Sign up to set email alerts
|

Role of Self-Stigma in Pathways from HIV-Related Stigma to Quality of Life Among People Living with HIV

Abstract: This study examined the relationships between perceived public stigma, experienced stigma, and quality of life in people living with HIV (PLHIV), and whether self-stigma mediates these relationships. Cross-sectional data were analyzed from 1704 PLHIV in care at OLVG hospital in the Netherlands. We measured different types of stigma (perceived public stigma, experienced stigma, and self-stigma), and various quality-of-life outcomes (disclosure concerns, depression, anxiety, sexual problems, sleeping difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…For internal consistency, all the studies, except a 4-item scale in one study [ 127 ] and some subscales in ten studies [ 23 , 52 , 68 , 69 , 91 , 111 , 170 , 172 , 176 , 189 ], reported Cronbach’s alphas of above the recommended acceptable threshold of 0.70 [ 191 ]. Two studies [ 34 , 95 ] reported the internal consistency of the HSS using McDonald’s omega instead of Cronbach’s alpha and reported good reliability ( Table 1 and Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For internal consistency, all the studies, except a 4-item scale in one study [ 127 ] and some subscales in ten studies [ 23 , 52 , 68 , 69 , 91 , 111 , 170 , 172 , 176 , 189 ], reported Cronbach’s alphas of above the recommended acceptable threshold of 0.70 [ 191 ]. Two studies [ 34 , 95 ] reported the internal consistency of the HSS using McDonald’s omega instead of Cronbach’s alpha and reported good reliability ( Table 1 and Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 36 A cross-sectional study in the Netherlands demonstrated the mediating effect of self-stigma on both perceived public stigma and experienced stigma on quality-of-life outcomes. 37 This is probable that “perceived beliefs” are potentially more likely to initiate feelings or fear of being stigmatized rather than the actual stigma experiences. 37 …”
Section: Discussionmentioning
confidence: 99%
“… 37 This is probable that “perceived beliefs” are potentially more likely to initiate feelings or fear of being stigmatized rather than the actual stigma experiences. 37 …”
Section: Discussionmentioning
confidence: 99%
“…We also have experience with a convergent parallel mixed methods approach, where qualitative and quantitative data are used in parallel to better understand a phenomenon. We are currently doing this in the context of a needs assessment for a self-stigma reduction intervention for PLHIV in the Netherlands (van der Kooij et al, submitted; van der Kooij et al, in preparation). Strictly speaking, data collection in these studies was not entirely parallel but data analyses were.…”
Section: Furthering Scientific Inquirymentioning
confidence: 99%